PENGARUH METODE TASK ANALYSIS TERHADAP KETERAMPILAN DALAM AKTIVITAS CUCI MOTOR PADA SISWA SLB N 1 YOGYAKARTA - Izhar Walayai; Yulian Agus Suminar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the challenges faced by students with intellectual disabilities at SLB N 1 Yogyakarta in mastering procedural skills, particularly in motorcycle washing. Students have difficulty systematically remembering the sequence of work steps and remain highly dependent on verbal instructions from teachers. This study aimed to test the effectiveness of the Task Analysis method in improving motorcycle washing skills in students. The method used in this study was an experiment with a pre-test and post-test design. The subjects were five tenth-grade SMALB students with intellectual disabilities at SLB N 1 Yogyakarta. Data collection was conducted through direct observation using a skills assessment instrument that had been tested for validity and reliability. Data analysis used descriptive statistics and the non-parametric Wilcoxon Signed Ranks Test. The results showed a significant improvement in students' motorcycle washing skills after the Task Analysis intervention. This was demonstrated by an increase in the average score from 67.42 in the pre-test to 82.57 in the post-test. The Wilcoxon test results showed a significance value (Asymp. Sig. 2-tailed) of 0.042 (<0.05), thus the null hypothesis (H₀) was rejected and the working hypothesis (H₁) was accepted. Therefore, it can be concluded that the Task Analysis method has a positive and significant effect on improving motorcycle washing skills among students at SLB N 1 Yogyakarta. This method is effective in helping students understand complex work steps into simpler parts so they can master them independently.